Tinjaun Mas?lah?ah atas Hak Khiyâr terkait Syarat Keperawanan - Khoirul Amin (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2015)
Marriage is a relationship between two people, so in a practical level, a horizontal line is also important to note. The filing requirement before marriage is already frequently encountered, but the filing requirement virginity filed by a husband is not yet prevalent. So this article is going to try to assess from the perspective mas?lah?ah related rights khiyâr acquired by a husband when it finds that his wife has no virginity again.